Enhancement in Tonically Active Glutamatergic Inputs to the Rostral Ventrolateral Medulla Contributes to Neuropathic Pain-Induced High Blood Pressure. (12th October 2017) - Wang, Wei; Zou, Zui; Tan, Xing; Zhang, Ru-Wen; Ren, Chang-Zhen; Yao, Xue-Ya; Li, Cheng-Bao; Wang, Wei-Zhong; Shi, Xue-Yin
Abstract : Neuropathic pain increases the risk of cardiovascular diseases including hypertension with the characteristic of sympathetic overactivity. The enhanced tonically active glutamatergic input to the rostral ventrolateral medulla (RVLM) contributes to sympathetic overactivity and blood pressure (BP) in cardiovascular diseases. We hypothesize that neuropathic pain enhances tonically active glutamatergic inputs to the RVLM, which contributes to high level of BP and sympathetic outflow. Animal model with the trigeminal neuropathic pain was induced by the infraorbital nerve-chronic constriction injury (ION-CCI). A significant increase in BP and renal sympathetic nerve activity (RSNA) was found in rats with ION-CCI (BP, n = 5, RSNA, n = 7, p < 0.05 ). The concentration of glutamate in the RVLM was significantly increased in the ION-CCI group (n = 4, p < 0.05 ). Blockade of glutamate receptors by injection of kynurenic acid into the RVLM significantly decreased BP and RSNA in the ION-CCI group (n = 5, p < 0.05 ). In two major sources (the paraventricular nucleus and periaqueductal gray) for glutamatergic inputs to the RVLM, the ION-CCI group (n = 5, p < 0.05 ) showed an increase in glutamate content and expression of glutaminase 2, vesicular glutamate transporter 2 proteins, and c-fos. Our results suggest that enhancement in tonically active glutamatergic inputs to the RVLM contributes to neuropathic pain-induced high blood pressure.